The English Culturalists: Interpreting Culture As A Social And Historical Process - Shigabutdinova Dina Yasaviyevna (Periodica Journal, 2026)
The article analyses the intellectual contribution of the English culturalists to the development of modern cultural studies. Formed within the social realities of post-war Britain, this tradition challenged restrictive definitions of culture and proposed an expanded analytical framework that includes everyday practices, popular forms of expression, and collective experience. By examining the ideas of Richard Hoggart, Raymond Williams, and E. P. Thompson, the study demonstrates how culture can be understood as a historically situated and socially produced process closely connected with power relations and human agency. The article also evaluates the relevance of English culturalist perspectives for contemporary humanities research.
Keywords: English culturalists; cultural analysis; everyday culture